Response to Palliative Esophageal Dilatation used in the Management of Dysphagia in Advanced Esophageal Cancer Jan 2014-March 2015 - M. Malik, Mohamed Ibrahim; Abdelrahman, Tahani Hassan; Ali, Moawia Mohamed; Omer, Sawsan Ahmed (مجلة الجزيرة للعلوم الصحية; مجلد 14 عدد 1 (2018), 2018)
The incidence of  esophageal cancer has risen in the last decades. Worldwide an estimated 456,000  cases and 400,000  deaths in 2012,  with male gender predominance. The aim of this study was to evaluate the response to palliative endoscopic dilatation used in management of locally advanced esophageal carcinoma in National Cancer Institute -University of Gezira and Gezira center for endoscopies and laparoscopic surgery in Wad -Medani Teaching Hospital. Retrospective  cross-sectional , case based hospital  study, from January 2014 to April 2015 including 108 esophageal cancer patients. It was found that one hundred and eight cases of esophageal cancer were diagnosed. 75 (69.4%) were females and 33 (30.6%) were male, with female to  male ratio of 2.3:1.Most  of them presented with locally advanced disease, 56 (51.9%) 58 (53.7%) of all patients underwent endoscopic esophageal dilatation. 36 (62.1%) of those patients underwent OGD dilatation before or after starting radiotherapy by variable time and some of them at the time of endoscopy. Improvement was seen in the dysphagia score in 20 (55.6%) of patients , the minimum duration of improvement was 1 week and the maximum was 2 months. 22 (37.9% ) of the patients received RT and underwent dilatation at the same period,  21(95.5%  ) of them improved,  3 weeks was the minimum and 6 months the maximum duration of improvement. 15 ( 25.9% )  were difficult dilation procedure because of long stricture. There were no significant complications.  Pain during the procedure was the common side effect in 40 (69%);  surgical emphysema in one patient(1.7%) and there were no complications in 17 (29.3%) of the dilated patiets. 31 (30.4%  ) has received RT alone, 23 (74.2% ) showed improvement in their swallowing ability,   the minimum duration of improvement was 3 weeks and the maximum was 7 months. 11 (  12.9% ) underwent second dilatation with apparent improvement in their swallowing ability. The results of the study were obtained from the patients till their last follow up or death. It was concluded that, esophageal cancer is more common among females . Almost all patients came with locally advanced disease and received palliative management. 53.7% underwent endoscopic dilatation, with apparent improvement in most of them especially if used in conjunction with radiotherapy to prevent post radiotherapy strictures,  with no significant complications during the endoscopic procedure, so the study concluded that the endoscopic dilatation , can be safely used in advance esophageal carcinoma when esophageal stenting is not available.